Pulmonary vein isolation with high power, short duration ablation leads to shorter procedure times associated with high success rates: a Prospective Randomized Trial. (19th May 2022) - Theis, C; Kaiser, B; Pirozzolo, G; Bekeredjian, R; Huber, C
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: The single procedure success rates of durable pulmonary vein isolation (PVI) for paroxysmal atrial fibrillation (AF) varies between 85 and 90 %. This prospective, randomized study investigated the efficacy of high power, short duration ablation in a temperature-controlled mode versus standard power settings in terms of single-procedure arrhythmia-free outcome, safety and procedural time. Methods and results: A total number of 176 patients undergoing de-novo catheter ablation for paroxysmal AF were randomized to two different treatment arms. In group-A patients, PVI was performed with RF-energy with standard power settings of 30 Watts in a temperature-controlled mode. The ablation procedure in group B was performed with RF-energy with higher power settings of 45 Watts. In both groups the ablation was performed with ablation index (AI) and following the CLOSE protocol (Biosense Webster Thermocool STSF). A total of 88 patients were randomized into each group without significant differences in baseline characteristics. During a mean follow-up of 12 ± 4 months after a single procedure, 79 (90%) patients of group A were free of arrhythmia recurrence versus 82 (93 %) patients in group B (p=ns). With regard to the procedural data, the procedure time was significantly shorter in group B (115.35 ± 15.38 versus 96.45 ± 17.19; p<0.01), the flouroscopy time and dose area were also significantly lower in Group B (9.66 ± 3.86 vs 5.45 ± 2.35; 330.84 ± 150.36 vs 202.51 ± 135.23) and total ablation times were significantly shorter in group B ((Table 1). Both procedures were performed with a low number of complications, no pericardial effusion was seen in either group, in both groups two patients had a significant hematoma of the groin with the need of surgical repair. Conclusions: RF-ablation with high power (45 Watts) in combination with ablation index and following the CLOSE protocol leads to shorter procedure times, a lower total ablation time and a good safety profile.